Assessment of new flow control strategy for the air handling units on energy management and sustainability - M.Ziya Sogut; Hamit Mutlu (International Journal of Thermofluids)
The issue of thermal control and energy-efficient air conditioning has emerged as a significant challenge in the context of industrial production. In particular, for processes that are aimed at decarbonisation, energy efficiency-based models provide an effective solution in the context of the energy transition. This study presents a proposal for the implementation of flow control in air handling units for the aforementioned facility. In this context, a case study was conducted on an air-handling unit with two different flow control management systems, namely a three-way valve and a flow control valve. The study demonstrated that the proposed flow control system for HVAC units exhibited an energy efficiency advantage of 31.08 % with respect to air conditioning temperature. Indeed, the implementation of flow control resulted in a 26.68 % gain in overall efficiency based on flow temperature. In conventional HVAC applications characterised by thermal fluctuations, energy flow control represents a valuable tool for optimising heat management, particularly during low-speed operation and across seasonal transitions. At the conclusion of the study, supplementary recommendations were formulated.